Comparison of standard prophylactic, intermediate prophylactic and therapeutic anticoagulation in patients with severe COVID-19: protocol for the ANTICOVID multicentre, parallel-group, open-label, randomised controlled trial. Issue 4 (26th April 2022) - Labbe, Vincent; Contou, Damien; Heming, Nicholas; Megarbane, Bruno; Ait-Oufella, Hafid; Boissier, Florence; Carreira, Serge; Robert, Alexandre; Vivier, Emmanuel; Fejjal, Mohamed; Doyen, Denis; Monchi, Mehran; et al.
Abstract : Introduction: COVID-19 induces venous, arterial and microvascular thrombosis, involving several pathophysiological processes. In patients with severe COVID-19 without macrovascular thrombosis, escalating into high-dose prophylactic anticoagulation (HD-PA) or therapeutic anticoagulation (TA) could be beneficial in limiting the extension of microvascular thrombosis and forestalling the evolution of lung and multiorgan microcirculatory dysfunction. In the absence of data from randomised trials, clinical practice varies widely. Methods and analysis: This is a French multicentre, parallel-group, open-label, randomised controlled superiority trial to compare the efficacy and safety of three anticoagulation strategies in patients with COVID-19. Patients with oxygen-treated COVID-19 showing no pulmonary artery thrombosis on computed tomography with pulmonary angiogram will be randomised to receive either low-dose PA, HD-PA or TA for 14 days. Patients attaining the extremes of weight and those with severe renal failure will not be included. We will recruit 353 patients. Patients will be randomised on a 1:1:1 basis, and stratified by centre, use of invasive mechanical ventilation, D-dimer levels and body mass index. The primary endpoint is a hierarchical criterion at day 28 including all-cause mortality, followed by the time to clinical improvement defined as the time from randomisation to an improvement of at least two points on the ordinal clinical scale. Secondary outcomes include thrombotic and major bleeding events at day 28, individual components of the primary endpoint, number of oxygen-free, ventilator-free and vasopressor-free days at day 28, D-dimer and sepsis-induced coagulopathy score at day 7, intensive care unit and hospital stay at day 28 and day 90, and all-cause death and quality of life at day 90. Ethics and dissemination: The study has been approved by an ethical committee (Ethics Committee, Ile de France VII, Paris, France; reference 2020-A03531-38). Patients will be included after obtaining their signed informed consent. The results will be submitted for publication in peer-reviewed journals. Trial registration number: NCT04808882 .